Analisis Ramalan Penjualan Iklan Jenis Jingle dan Add Lips Pada PT. Radio Berita Kaltim (Antara News Radio) Samarinda - Heriyanto Heriyanto (Prodi Ilmu Administrasi Negara, 2016)
This study aims to determine which method is most appropriatebetween the Method of Least Squares (Least Square Method) andMethods Semi average (Semi Average Method) are on StandardError Forecasting (SKP) Smallest in the sale of advertising inparticular types of jingles and add lips the period 2010 / 2011.Formulation of the problem in this research is: